Miniaturizable Phase-Sensitive Amplifier Based on Vector Dual-Pump Structure for Phase Regeneration of PDM Signal - Shuaiwei Jia; Zhuang Xie; Wen Shao; Xiaotian Han; Yulong Su; Jiacheng Meng; Duorui Gao; Wei Wang; Xiaoping Xie (IEEE Photonics Journal, 2024)
Phase sensitive amplification is indispensable in promoting applications such as all-optical regenerators, quantum communications, all-optical analog-to-digital conversion, and long-distance communications. In this article, we proposed a vector dual-pump nondegenerate phase-sensitive amplification scheme based on ultra-silicon-rich nitride (Si7N3) waveguide, and theoretically verified its capability for all-optical regeneration of phase-encoded polarization-division multiplexing (PDM) signal without the need for complex polarization diversity structures. We achieved a gain extinction ratio (GER) of ∼37.5 dB by using a 3-mm-long Si7N3 waveguide with a high nonlinear coefficient (∼279 /W/m). Signal quality before and after regeneration is characterized by constellation diagram and error vector magnitude (EVM). The results show that the EVM of the degraded PDM differential phase-shift keying (DPSK) signals with two polarization states of 54% and 53.8%, can be improved to 13.6% and 13.6%, respectively, after regeneration, directly illustrating the remarkable phase noise suppression effect. The applicability of the scheme in PDM quadrature phase shift keying (QPSK) signals was further investigated. Similarly, the EVMs of the two polarization states of the deteriorated QPSK signals are optimized from 28.9% and 29.3% to 13.7% and 13.9%, respectively. The proposed scheme has promising applications in integrated all-optical processing systems and long-distance transmission of optical communications.